(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the association of Doppler ultrasound with clinical andrological examination to identify the reproductive quality of stallions in paraiban swamp region. Eleven horses were used, aged between three and 27 years. The ejaculates were collected by the artificial vagina method and the seminal samples were submitted to field evaluation (subjective motility, cellular integrity) and in the laboratory (objective motility, cellular integrity). After seminal collection, the animals were submitted to testicular blood flow evaluation with Doppler ultrasound. Differences (P<0.05) were observed between the parameters of subjective motility, field-evaluated, and objective motility, in the laboratory. The integrity of the sperm plasma membrane was similar in field and laboratory tests. In the ultrasound parameters, it was observed that the Pulsatility Index has a positive correlation with lateral head displacement amplitude (ALH) of the spermatozoa. Finally, when evaluating age parameter, elderly animals presented reduced motility and lower blood supply in the testicular region, resulting in low fertility. It is concluded that the clinical andrological examination, when isolated, does not determine the fertile capacity of stallions; doppler-associated ultrasound identifies subfertile animals and can be an auxiliary tool in the stallions selection.